BIBLICKÁ BABYLONSKÁ VEŽA A ANTICKÍ ĽUDIA. HĽADANIE VLASTNÝCH PREDKOV V STREDOVEKU - GRZESIK, RYSZARD (Slavia Antiqua. Rocznik poświęcony starożytnościom słowiańskim, 2020)
The article is a presentation of ethnogenesis of Slavs in the view of medieval chronicles. Hungarian medieval historiography served as a starting point of the reflection. The author describes how national “Prehistory” was presented in Hungarian chronicles and compares them with the general tendencies in medieval historiography to show the way in which native origins were created. It was a search for a common ascendant of the European people based on the Bible figure of Japhet and the way in which this tradition is related to facts known from ancient history (like the Trojan War) as well as geographical description based on ancient erudition. It was the common explanation of native origins in the entire Western and Eastern Christianity.As a result, the culture of medieval and Pre-Modern Europe united despite the political divisions.